Technologies of adaptive management as a mechanism for ensuring the stability of the development of companies - Nataliia Obukhova; Oksana Davydenko (Фінансово-кредитні системи: перспективи розвитку., 2024)
In this article, the essence of technologies, characteristics and analysis of the phases of business process implementation in project activity under adaptive management are established. Project structuring, allocation of main tasks based on systems theory and development of a functional project management system as a whole become important in adaptive management. It is necessary to consider the activities of development companies comprehensively, relying on the organizational structure through the preparation of real plans, based on the knowledge of all specialists - executors of the works. The activities of companies are clearly structured into processes, which in turn are divided into functions. At the same time, all participants in any project activity are the main elements of the company's structure, as they ensure the practical implementation of the idea and concept. Present-day problems in the organization and management of development companies that arise under the conditions of the functioning of business processes are revealed. Adaptive management is characterized by the choice of a financing strategy for the companies' activities. But it consists in ensuring, through certain actions, the closure of financing needs and the transition from the current capital structure to the future one. In this situation, one-part and parallel use of different funding sources and schemes occurs. The authors indicated the formation of mechanisms for the stable functioning of companies through a process approach. The environment has an impact on the implementation of any project: it is necessary to be able to determine, calculate and take into account the impacts: economic, social, financial, managerial, technological, technical and execution terms, that is, the external and internal environment. Under certain conditions, each of these impacts can be critical for the project and lead to its liquidation. The article notes that all information from all those responsible for business processes are formed into a single industry model that ensures stable functioning. The authors attach an important place to the information system of management, accounting, analysis of project implementation, actualization of problems of operational plans and professionalism of specialists. New approaches and improved methodology for ensuring the stability of the functioning of companies using adaptive management are proposed.